2018
DOI: 10.3892/mco.2018.1582
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of unintentional body weight loss in colon cancer patients

Abstract: The aim of the present study was to investigate whether unintentional body weight loss (BWL) provides additional clinical information in terms of tumor progression and prognosis in non-metastatic colon cancer. In the present study, a total of 2,406 consecutive colon cancer patients without metastasis were retrospectively enrolled. Unintentional BWL was defined as loss of >5% of body weight within the last 6–12 months, or defined subjectively upon fulfillment of at least two of the following: Evidence of change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 19 publications
0
9
1
Order By: Relevance
“…In addition to skeletal muscle loss, body weight loss derived from cancer cachexia and malnutrition is reported to be associated with a poor prognosis for several malignancies. [6][7][8][9][10] However, body weight loss was not associated with poor OS in our cohort. Skeletal muscle loss may be a more accurate prognostic marker than body weight loss because skeletal muscle loss and adipose tissue gain can occur simultaneously 13 ; consequently, body weight loss may not be reflected by sarcopenia status.…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…In addition to skeletal muscle loss, body weight loss derived from cancer cachexia and malnutrition is reported to be associated with a poor prognosis for several malignancies. [6][7][8][9][10] However, body weight loss was not associated with poor OS in our cohort. Skeletal muscle loss may be a more accurate prognostic marker than body weight loss because skeletal muscle loss and adipose tissue gain can occur simultaneously 13 ; consequently, body weight loss may not be reflected by sarcopenia status.…”
Section: Discussioncontrasting
confidence: 49%
“…Our data support the findings regarding the prognostic significance of skeletal muscle loss during NAC in the population not including obese patients. In addition to skeletal muscle loss, body weight loss derived from cancer cachexia and malnutrition is reported to be associated with a poor prognosis for several malignancies 6–10 . However, body weight loss was not associated with poor OS in our cohort.…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…However, the relation between ALB and WL remains controversial. Kuo et al22 reported WL was significantly associated with ALB in colon cancer patients. However, Unal et al23 revealed that there was no significant difference between the WL and ALB in patients with head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Unintentional weight loss is defined as >5% of body weight loss within 6–12 months. Malignancies, particularly GI cancers, are diagnosed in approximately 25% of patients who present with unintentional weight loss [13,14,15]. Moreover, the highest frequency of weight loss is seen among the patients with pancreatic or gastric cancer [16,17].…”
Section: Introductionmentioning
confidence: 99%